Overview of Dietary Patterns and Nutritional Status of Children Aged 24–59 Months at Tumbuan Health Center, Seluma - Maysara Dwi Alfiana; Suryani, Desri; Risda Yulianti (CV. CENDIKIA JENIUS INDONESIA, 2025)
Nutritional Nutritional status is an important indicator in determining the level of health and growth of children. A good diet plays a role in meeting nutritional needs and contributing to the quality of early childhood health. This study aims to determine the description of the diet and nutritional status of children aged 24–59 months in the working area of ​​the Tumbuan Health Center UPT, Seluma Regency. This study used a descriptive design with a cross-sectional approach. The number of samples was 52 mothers who had children aged 24–59 months who were selected using a purposive sampling technique. Data were collected through a food frequency questionnaire (FFQ) and nutritional status measurements using body weight and height, then analyzed univariately. The results showed that most children had a good diet, with fairly good consumption of animal and vegetable protein. As many as 90.4% of children had a weight according to age in the normal category, 84.6% had a height according to age in the normal category, and 82.7% had good nutritional status based on weight according to height. Conclusion: The majority of children aged 24–59 months have good eating patterns and normal nutritional status based on weight, height, and weight to height. It is recommended that parents increase their nutritional knowledge and routinely monitor their children's growth through the nearest health service.